2014
DOI: 10.1089/vbz.2013.1521
|View full text |Cite
|
Sign up to set email alerts
|

Serological Anthrax Surveillance in Wild Boar (Sus scrofa) in Ukraine

Abstract: Anthrax, caused by Bacillus anthracis, is an acute disease affecting wildlife, livestock, and humans worldwide, although its impact on these populations is underappreciated. In Ukraine, surveillance is passive, and anthrax is often detected in livestock. However, wildlife is not subject to surveillance, although anthrax deaths (such as in wild boar, Sus scrofa) have been documented. The wild boar is a plentiful and widespread species in Ukraine and is frequently hunted. We initiated a screening study testing U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…This tool could help understanding anthrax ecology in the apparent absence of disease. It could also potentially be used to determine the status of anthrax in areas where the disease presence or absence is uncertain due to lack of reported outbreaks in livestock species, given the missed cases or under reporting of outbreaks by communities [2, 18]. Such information would augment the surveillance measures for anthrax already outlined by WHO/OIE [9, 16], for better understanding the range of the disease [18, 19, 35] and hence targeted public health awareness campaigns and preventive livestock vaccinations where warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tool could help understanding anthrax ecology in the apparent absence of disease. It could also potentially be used to determine the status of anthrax in areas where the disease presence or absence is uncertain due to lack of reported outbreaks in livestock species, given the missed cases or under reporting of outbreaks by communities [2, 18]. Such information would augment the surveillance measures for anthrax already outlined by WHO/OIE [9, 16], for better understanding the range of the disease [18, 19, 35] and hence targeted public health awareness campaigns and preventive livestock vaccinations where warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In highly susceptible hosts like herbivores, the course of anthrax is usually peracute to acute with high mortality in affected individuals, making serology of little value as a method of laboratory diagnosis, except only for the purpose of monitoring vaccine efficacy [16, 17]. However, carnivores and suids have been found to be relatively resistant, produce antibodies to B. anthracis and could even be reactive to unapparent infections in the range [8, 18]. Although the length of the reactive immunity in the affected carnivores has not yet been determined, it is suspected to be longer than a year, as compared with a few months in herbivores [2, 6] thus potentially enabling detection of antibodies to B. anthracis in these animals well after the disease event [8, 19].…”
Section: Introductionmentioning
confidence: 99%
“…An additional published collaborative study highlights the importance of including wildlife and surveillance for zoonotic diseases ( 30 ). In that study, the serological survey of wild boar collected from hunter check stations confirmed that at least some boars are exposed to B. anthracis in Ukraine.…”
Section: Pathogens and Policiesmentioning
confidence: 99%
“…On the other hand, the relatively low seroprevalence in combination with high mortality rates, which are observed in savanna herbivores, suggests these species are more susceptible to the disease [ 10 , 16 ]. Bagamian et al [ 18 ] used such logic to call for the broad combination of postmortem data with serological surveillance, specifically in non-savanna ecosystems, to further assess the dynamics of anthrax disease [ 16 ].…”
Section: Introductionmentioning
confidence: 99%